Potensi Lahan Rawa untuk Mendukung Ketahanan Pangan Nasional - Zainal Ridho Djafar (Seminar Nasional Lahan Suboptimal, 2019)
The potential of swamp land to support national food security has been studied through a desctiptive study. The area of swamp land in Indonesia is estimated at around 34 million hectares. The land consists of tidal swamps of around 60% and the remaining is swamp lowland of about 40%. The land spreads from the island of West Papua in the east to Sumatera in the western part of Indonesia. Of that swamp land area, about 14 million hectares is suitable for agricultural crops. Form the total of swampy area, about 4,92 million hectares has been cultivated for rice plants and around 5,04 million more hectares is suitable for expansion of rice cultivation development. The productivity of swamp land is quite low at around 2-3 tons/ha of hasvested dry grain (HDG). With land improvement, the productivity can be increased to 5-7 tons/ha of HDG. The development of the potential of swamp land can be improved through water management and land improvement technology. This technology is followed by extensification and intensification activities on the land that has been cultivated and the land which is potential for the development of rice plants. The results of the study reveal that with water control and land improvement, the extensification could be increased from 10 million hectares to 20-30 million hectares per year. Rice production is increased from 30 million tons to 60-90 million tons of rice per year. This means that swamp lands have fairly high potential to support national food security.